2015
DOI: 10.1080/1331677x.2015.1041778
|View full text |Cite
|
Sign up to set email alerts
|

Profit persistence and determinants of bank profitability in Croatia

Abstract: The aim of this research was to determine the persistence of profit in an emerging banking sector of the Republic of Croatia. Most developing countries have experienced common changes within restructuring of the banking system and therefore, this issue has become crucial, especially after comparing poor empirical findings in these countries to the findings of developed countries. However, research related to this issue is non-existent in the Croatian banking sector. Moreover, among the few studies that were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 19 publications
(21 reference statements)
11
62
0
Order By: Relevance
“…However, no impact of credit risk, bank size and fees income were noted. Furthermore, Pervan et al (2015) studied the Croatian banks' profitability determinants using a panel data of 46 Croatian banks from 2002 to 2010. The results concluded a positive influence by industry concentration, lagged profitability, intermediation, bank size, capital risk, GDP and market growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, no impact of credit risk, bank size and fees income were noted. Furthermore, Pervan et al (2015) studied the Croatian banks' profitability determinants using a panel data of 46 Croatian banks from 2002 to 2010. The results concluded a positive influence by industry concentration, lagged profitability, intermediation, bank size, capital risk, GDP and market growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these variables are ownership concentration (Agostino et al, 2005), the extent and types of regulation (Amidu and Harvey, 2016;Chronopolous et al 2015), loan loss provision (Amidu andHarvey, 2016, financial crisis (Chronopolous et al 2015), market entry restrictions, market concentration, the prevailing level of competition (Goddard et al, 2011), and bank capitalization (Gugler & Peev, 2018). Intriguingly, Pervan et al (2015) found that the persistence of bank profitability is not necessarily determined by exogenous factors but by the level of bank profitability itself.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Pervan, Pelivan and Arneric (2015) conclude that the statistically signifi cant variables with a positive infl uence on bank's profi tability are the following: profi tability from the previous year, bank size, solvency risk, intermediation, industry concentration, market growth and GDP growth; while variables of credit risk, infl ation and operating expenses management have negative and statistically signifi cant impact on profi tability. Previous research indicated that the correlation between corporate governance and bank performance is still not clearly established and the research results are quite diverse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The size variable can be measured as the natural logarithm of total assets of each analysed bank. Also according to Pervan, Pelivan and Arneric (2015) we can dived banks into four basic groups, unprofi table banks those who have a negative value of return on asset, low profi table banks whose return on asset takes the up to 1%, moderately profi table banks whose return on asset in in the range between 1% and 2% and profi table banks whose return on asset is higher than 2%. Furthermore, it is recommended to use some control variables such as profi tability of banks in the previous period, natural logarithm of market capitalization, solvency risk, board size in the turns of natural logarithm of number of members in board, non-executive director's calculated as total non-executive directors by total member in boards, leverage calculated by total debts over total equity and previously mentioned bank size calculated by natural logarithm of total assets.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%